2009
DOI: 10.2298/pif0903203m
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spiromesifen on the reproductive potential of Tetranychus urticae koch (Acari: Tetranychidae)

Abstract: SUMMARYLaboratory bioassays were conducted to evaluate the effects of spiromesifen on the fecundity, fertility and population growth of two-spotted spider mite (Tetranychus urticae Koch) after treatment of pre-ovipositing females with five acaricide concentrations: 180 mg/l (maximum recommended concentration for use in glasshouses against spider mites), 18 mg/l, 1.8 mg/l and 0.18 mg/l (the last one was discriminative for eggs and immatures in preliminary studies, i.e. produced 100% mortality of those stages) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Meanwhile, (Marcic et al 2010) showed that spiromesifen at different concentrations had a significant negative impact on the fecundity and net fertility of T. urticae. In another study, Marcic et al (2009) recorded that the two-spotted spider mite population growth rates and fecundity were significantly reduced after exposure with spiromesifen. Besides, Marcic (2007) reported that spirodiclofen significantly affected the survival rate and total fecundity of T. urticae.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, (Marcic et al 2010) showed that spiromesifen at different concentrations had a significant negative impact on the fecundity and net fertility of T. urticae. In another study, Marcic et al (2009) recorded that the two-spotted spider mite population growth rates and fecundity were significantly reduced after exposure with spiromesifen. Besides, Marcic (2007) reported that spirodiclofen significantly affected the survival rate and total fecundity of T. urticae.…”
Section: Discussionmentioning
confidence: 97%